Interpreting Psalm 22: Collective Suffering and National Hope in the Indonesian Context - Tanasyah, Yusak; Kurniawan, Mieke Cynthia; Hutapea, Jusuf (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2025)
This article explores the significance of Psalm 22, particularly the poignant cry,